2018
DOI: 10.1073/pnas.1718917115
|View full text |Cite
|
Sign up to set email alerts
|

Shortwave infrared fluorescence imaging with the clinically approved near-infrared dye indocyanine green

Abstract: Fluorescence imaging is a method of real-time molecular tracking in vivo that has enabled many clinical technologies. Imaging in the shortwave IR (SWIR; 1,000–2,000 nm) promises higher contrast, sensitivity, and penetration depths compared with conventional visible and near-IR (NIR) fluorescence imaging. However, adoption of SWIR imaging in clinical settings has been limited, partially due to the absence of US Food and Drug Administration (FDA)-approved fluorophores with peak emission in the SWIR. Here, we sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
569
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(611 citation statements)
references
References 68 publications
(75 reference statements)
10
569
2
2
Order By: Relevance
“…Spectroscopic characterization of this NIR‐I (650–900 nm) dye reveals a long‐emission tail that stretches into the NIR‐II region over 1000 nm. This finding highlights the possibility of using conventional NIR‐I dyes for NIR‐II imaging . Further imaging studies using commercially available NIR‐I dyes clearly demonstrate the success of this strategy, opening an entirely new route to realize NIR‐II imaging in preclinical research and even clinical imaging .…”
Section: Introductionmentioning
confidence: 70%
“…Spectroscopic characterization of this NIR‐I (650–900 nm) dye reveals a long‐emission tail that stretches into the NIR‐II region over 1000 nm. This finding highlights the possibility of using conventional NIR‐I dyes for NIR‐II imaging . Further imaging studies using commercially available NIR‐I dyes clearly demonstrate the success of this strategy, opening an entirely new route to realize NIR‐II imaging in preclinical research and even clinical imaging .…”
Section: Introductionmentioning
confidence: 70%
“…Although the peak emission of donor–acceptor–donor (D‐A‐D) dyes and the tail emission of cyanine dyes can be both used for NIR‐II imaging, the benefit of NIR‐II imaging is better realized in the NIR‐IIb sub‐window (>1500 nm), where light can penetrate nearly all tissues . Imaging in the NIR‐IIb window can minimize photon scattering and simultaneously avoid high absorbance by water, affording high resolution of mouse vasculature at depths of several millimeter in the brain or other tissues .…”
mentioning
confidence: 99%
“…1a), a probe that is readily available and is approved by US Food and Drug Administration (FDA). ICG has been previously used in humans as a typical NIR-I fluorophore (for studies of liver and retina) 2,3,40 , and, as been previously shown, also offers the advantage of bright NIR-II fluorescence emission 31 .…”
Section: Resultsmentioning
confidence: 98%
“…Here, we report the development of two NIR-II fluorescence microscopes adapted to brain imaging of large animals. Using a clinically approved dye named indocyanine green (ICG) as a bright NIR-II fluorescent probe 31,32 in rhesus macaques, we demonstrate that the wide-field NIR-II fluorescence microscope offers high temporal resolution 23 , sufficient for realizing real-time imaging of cerebral blood vessels and achieving measurement of CBF velocity and cardiac cycle. The second microscope, a confocal NIR-II fluorescence microscope, offers high spatial resolution and high SBR (signal to background ratio) via optical sectioning capability 33 , enabling reconstruction of a clear three-dimensional volume of cortical vasculature up to an imaging depth of ~500 μm.…”
Section: Introductionmentioning
confidence: 99%